2006
DOI: 10.1302/0301-620x.88b2.16906
|View full text |Cite
|
Sign up to set email alerts
|

Are systemic emboli reduced in computer-assisted knee surgery?

Abstract: We undertook a prospective, randomised study using a non-invasive transcranial Doppler device to evaluate cranial embolisation in computer-assisted navigated total knee arthroplasty (n = 14) and compared this with a standard conventional surgical technique using intramedullary alignment guides (n = 10). All patients were selected randomly without the knowledge of the patient, anaesthetists (before the onset of the procedure) and ward staff. The operations were performed by a single surgeon at one hospital usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 33 publications
4
81
0
2
Order By: Relevance
“…Advocates of conventional TKA cite the increased operative and tourniquet times [24][25][26] associated with navigated TKA, whilst proponents of navigated TKA have yet to identify a significant clinical advantage over conventional TKA that justifies the significant hardware costs perceived to be associated with using such techniques [27]. Studies do exist which show reduced blood loss [14,28,29], fewer systemic emboli [24,30,31] and fewer clinically detectable thromboembolic events [32] in navigated TKA compared with conventional TKA, and this is thought to be directly related to the avoidance of femoral and/or tibial intramedullary instrumentation.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Advocates of conventional TKA cite the increased operative and tourniquet times [24][25][26] associated with navigated TKA, whilst proponents of navigated TKA have yet to identify a significant clinical advantage over conventional TKA that justifies the significant hardware costs perceived to be associated with using such techniques [27]. Studies do exist which show reduced blood loss [14,28,29], fewer systemic emboli [24,30,31] and fewer clinically detectable thromboembolic events [32] in navigated TKA compared with conventional TKA, and this is thought to be directly related to the avoidance of femoral and/or tibial intramedullary instrumentation.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
“…Studies do exist which show reduced blood loss [14,28,29], fewer systemic emboli [24,30,31] and fewer clinically detectable thromboembolic events [32] in navigated TKA compared with conventional TKA, and this is thought to be directly related to the avoidance of femoral and/or tibial intramedullary instrumentation. Cohorts in all these studies were, however, very small and offer low levels of evidence, and contradictory evidence does exist showing no difference in blood loss [25,33] and thromboembolic phenomena [13] between the two groups.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
“…The risk of fat embolism during knee replacement has been shown to be significantly reduced when an extramedullary femoral alignment guide [27] or computerassisted surgery is used [7,15]. Studies using non-invasive [15] and invasive monitoring [7] have shown that significantly fewer emboli are detected in the systemic circulation during computer-assisted TKR compared with conventional TKR.…”
Section: Embolic Eventsmentioning
confidence: 99%
“…Studies using non-invasive [15] and invasive monitoring [7] have shown that significantly fewer emboli are detected in the systemic circulation during computer-assisted TKR compared with conventional TKR. However, most studies comparing these two methods have not shown any significant difference in post-operative thromboembolic events [2].…”
Section: Embolic Eventsmentioning
confidence: 99%
See 1 more Smart Citation